(untitled) (Research, Society and Development, 2020)
This is an ecological study design of multiple groups that aims to present the notifications profile of intimate partner violence during pregnancy (IPVP), based on the Notifiable Diseases Information System (SINAN) database. Furthermore, the IPVP records time trend on Brazilian capitals and its distribution by major regions between 2009 and 2016 were verified. Totally, 1,201 IPVP cases were registered in Brazilian capitals in 2016, which 39% reported psychological/moral violence, 69% physical violence, 28% sexual violence and 34% reported more than one of the subtypes of violence mentioned above. The Northeast and Southeast regions showed the highest prevalence’s IPVP at which it was reported more than one subtype of violence, 42% and 43% respectively. In conclusion, although notifications of violence against women during pregnancy has been recently growing years, the data are still incipient, and underreporting is a reality to be overcome in Brazil. In this context, this study generates additional technical knowledge and highlights the needs for more effective public policies to struggle this major problem and its consequences.